2015
DOI: 10.21134/haaj.v15i2.244
|View full text |Cite
|
Sign up to set email alerts
|

Sustancias nocivas y clima motivacional en relación con la práctica de actividad física

Abstract: La adolescencia es un periodo crítico en cuanto a la adquisición de hábitos saludables en detrimento de las conductas dañinas, por ello el presente estudio tiene como objetivo analizar el clima motivacional hacía la actividad física, el consumo de alcohol y tabaco, y establecer las relaciones existentes entre las variables. Participaron 2.134 estudiantes de edades comprendidas entre los 15 y los 18 años (M=15,93 años), que permitió el registro y evaluación de las variables Consumo de Tabaco (FTND), Consumo de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
10
0
5
Order By: Relevance
“…This research aims to define the motivational climate and its relationship with self-concept and resilience in a sample of primary schoolchildren in fifth and sixth grade primary education. In general terms, the literature shows similar studies carried out on university students and adolescents in the field of physical sports activity [17,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…This research aims to define the motivational climate and its relationship with self-concept and resilience in a sample of primary schoolchildren in fifth and sixth grade primary education. In general terms, the literature shows similar studies carried out on university students and adolescents in the field of physical sports activity [17,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Castro-Sánchez et al (2015) and Chacón et al (2017b) demonstrated a direct connection between motivational climate in sport and alcohol and tobacco consumption in teenagers, as well as the use of video games in emerging adulthood, coming to the conclusion that goals oriented toward ego were associated with harmful habits. However, no studies have been found analyzing existing fluctuations in relations between motivational climate in sport and harmful habits regarding kind of sport practiced, leaving a fertile field of study that will help in the setting of patterns and definition of features leading to these kinds of habits.…”
Section: Introductionmentioning
confidence: 95%
“…Asimismo, se ha demostrado cómo el estilo de vida y factores motivacionales ejercen una influencia directa en el logro académico. De hecho, Alfonso (2016) y Ayan, Besada, Cancelas y no sólo muestran una relación directa entre práctica deportiva y un mejor rendimiento académico mediante la eliminación de estados de ansiedad y estrés, sino también de forma indirecta; pues un estilo de vida activo se desvincula de conductas no saludables asociadas a bajo desempeño escolar, como el consumo de sustancias nocivas (Castro-Sánchez et al, 2015;Lisha y Sussman, 2010).…”
Section: Introductionunclassified